COOPERATION BETWEEN THE FAMILY AND PRESCHOOL EDUCATIONAL ORGANIZATIONS IN RAISING THE YOUNGER GENERATION (Multidisciplinary Journal of Science and Technology, 2026)
The upbringing and development of children require the coordinated efforts of various social institutions, among which the family and preschool educational institutions play the most significant roles. Effective cooperation between these institutions creates favorable conditions for the comprehensive development of children, supports their socialization, and contributes to the formation of moral values and positive behavior. This article examines the importance of partnership between families and preschool educational institutions in the upbringing of the younger generation. The study highlights the principles, forms, and benefits of collaboration, as well as the role of educators and parents in creating a supportive educational environment.